1989
DOI: 10.1159/000125110
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Distribution of Delta Sleep Inducing Peptide in the Rabbit Brain and Hypophysis

Abstract: The distribution of delta sleep inducing peptide (DSIP) in the rabbit brain has been studied with immunohistochemical techniques. DSIP-like immunoreactivity was predominantly detected in the basal forebrain, hypothalamus and hypophysis. Even in colchicine-pretreated animals, immunolabeled cell bodies were relatively few. They were mostly scattered through the ventrolateral septum, the diagonal band of Broca and preoptic areas. Clusters of positive cell bodies were also found in the arcuate nucleus and adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…level, and extend previous immunohistochemical studies in rabbit brain where DSIP-like immunoreactivity has been frequently detected in GnRH-containing neurons [4,13]. Since the first evidence of the colocalization of several neurotransmitters in single neuronal cell bodies [25], many attempts have been made to immunohistochemically demonstrate the colocalization of signal substances in the nervous systems an d /o r peripheral organs [26,27].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…level, and extend previous immunohistochemical studies in rabbit brain where DSIP-like immunoreactivity has been frequently detected in GnRH-containing neurons [4,13]. Since the first evidence of the colocalization of several neurotransmitters in single neuronal cell bodies [25], many attempts have been made to immunohistochemically demonstrate the colocalization of signal substances in the nervous systems an d /o r peripheral organs [26,27].…”
Section: Discussionsupporting
confidence: 80%
“…DSIP immunoreactivity is widely distributed in biological fluids, brain and glandular system of several species [4][5][6][7][8]. Besides some sleep-promoting effects [1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staining was not seen in controls using preimmune serum or secondary antibodies alone. Characteristics and details o f preparation of primary antibodies have been extensively described elsewhere [10,11]. Antiserum to DSIP was inactivated by preincubation with synthetic DSIP, but not with LH-RH and pre-pro-LH-RH precursor fragments, adrenacorticotropic hor mone and derivative fragments, thyrotropin-releasing hormone, vaso pressin, angiotensin II, and leukotriene C4 previously immunohistochemically localized within LH-RH neurons [22], Preincubation of anti serum to LH-RH with LH-RH totally abolished the immunoreactivity, whereas preincubation with DSIP or the peptidic hormones mentioned above had no effect.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoreactive DSIP has been found in biological fluids, the brain and endocrine glands of several species [6][7][8]. Recent immu nocytochemical studies using light and electron microsco-py have shown that in the adult DSIP colocalizes with GnRH in neurons of several species including man [9], rabbit [10], guinea pig [11] and rat [12].…”
Section: Introductionmentioning
confidence: 99%